ANALISIS ASUHAN KEPERAWATAN PADA PASIEN GANGGUAN PERNAFASAN AKIBAT PENYAKIT PARU OBSTRUKTIF KRONIK (PPOK) DISERTAI EKSASEBRASI AKUT DENGAN PENERAPAN INTERVENSI BATUK EFEKTIF TERHADAP BERSIHAN JALAN NAFAS TIDAK EFEKTIF DI RUANG ICU RSUD CILILIN TAHUN 2026 - Novianti, Fitri; Sutisna, M. Iqbal; Manalu, Lisbet Octovia; Rustandi, Budi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Chronic Obstructive Pulmonary Disease (COPD) is a chronic lung disease characterized by progressive and not fully reversible airflow limitation. This condition can cause impaired gas exchange leading to chronic hypoxia. Prolonged hypoxia may increase pressure in the pulmonary blood vessels, thereby increasing the workload of the heart, especially the right ventricle, which can eventually lead to cardiac enlargement or Cardiomegaly. Therefore, appropriate nursing care is needed to manage the problems that arise in patients with COPD and cardiomegaly. Objective: To identify and implement nursing care in patients with COPD and cardiomegaly through the nursing process which includes assessment, nursing diagnosis, planning, implementation, and evaluation. Methods: This scientific paper used a case study method with a nursing process approach that includes assessment, determination of nursing diagnoses, planning of nursing interventions, implementation, and evaluation in patients with COPD and cardiomegaly. Results: The results of the nursing care implementation showed that the main nursing problems found in the patient were ineffective airway clearance, impaired gas exchange, and decreased cardiac output. Nursing interventions included monitoring respiratory status, positioning the patient in a semi-Fowler position, deep breathing exercises, effective coughing techniques, and oxygen therapy as indicated. After the nursing interventions were implemented, the patient’s condition improved as indicated by reduced shortness of breath and improved breathing pattern. Conclusion: Nursing care for patients with COPD and cardiomegaly can help overcome nursing problems and improve the patient’s health condition through appropriate and continuous nursing interventions.